Numerical simulation of high strength circular double-skin concrete-filled steel tubular slender columns. (1st August 2018) - Liang, Qing Quan
Highlights: A mathematical model is presented for simulating circular DCFST slender columns. Incremental nonlinear equilibrium equations are solved using Müller's method. Accurate material laws for sandwiched concrete in circular tubes are described. The behavior of high strength circular DCFST slender columns is investigated. The model presented is shown to be an accurate simulation tool for DCFST columns. Abstract: Circular double-skin concrete-filled steel tubular (DCFST) slender columns made of high-strength concrete are high performance structural members with wide applications in engineering structures. However, research studies on the behavior, load distributions in concrete and steel components and confinement characteristics of such composite columns under eccentric loading have been very limited. This paper describes a new mathematical model that computes the axial load-deflection performance of high-strength circular DCFST slender columns subjected to eccentric loading. The incremental nonlinear equilibrium equations of DCFST slender columns are solved by the developed efficient computational procedure and numerical solution algorithms accounting for initial geometric imperfections and second order effects. The mathematical model incorporates the accurate material constitutive laws of sandwiched concrete, which accurately predict the residual concrete strength and strain in the post-yield regime. The computer program implementing the mathematical model is utilized to quantify the influences of geometric and material properties and concrete confinements on the load-deflection behavior, column strength curves and load distributions in circular DCFST slender columns. It is shown that the mathematical model not only accurately predicts the experimental behavior of circular DCFST slender columns but also effectively monitors the load distributions in concrete and steel components of DCFST slender columns under deflection increments. The proposed mathematical model is an accurate and efficient computational and design technique for circular DCFST slender columns.